BIOGARDEN BERBASIS RUMPUT VETIVER UNTUK PENGOLAHAN AIR LIMBAH PROSES PENGOLAHAN KOPI: SOLUSI INOVATIF UNTUK LINGKUNGAN BERKELANJUTAN DI SAWANGAN, MAGELENG - Mardhatilah, Dina; Afroda, Helmi; Faizah, Kuni; Firmansyah, Eric (Gapenas Publisher, 2025)
The empowerment of farmers in Ketep Village, Sawangan, Magelang is an important step to increase their independence, creativity, and productivity. In addition to being involved in coffee processing, farmers in this area are also active in vegetable cultivation. However, the coffee processing process produces liquid waste with a very acidic pH if it is directly discharged into water bodies or soil, which can damage the environment and negatively impact the quality of the plants grown and endanger consumer health. Coffee liquid waste contains high organic matter, which can increase Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) in waters if disposed of carelessly. To overcome this problem, we propose a community service program that utilizes vetiver-based biogardens as a method of liquid waste management. As a PKM partner in this service is the